The Concept of Spiritual Education in Surah Ibrahim Verses 35-41 According to Muhammad Quraish Shihab - Aulia Fitri Yunus; Sidik Sidik; Kamaruddin Kamaruddin (Department of Islamic Education, Postgraduate Program State Institute for Islamic Studies Palu, 2019)
This researcher examines the concept of spiritual education according to Muhammad Quraish Shihab in surah Ibrahim verses 35-41 and the relevance of spiritual education in the present context. This type of research is library research and data collection is done by the method of irfani (Sufism) and analysis approach. Data analysis was performed with inductive analysis techniques, which are drawing conclusions by departing from specific interpretations towards general conclusions. While interpretative is to look for the meaning behind the explicit and implied meaning. The results of the research show that the concept of spiritual education according to Muhammad Quraish Shihab in surah Ibrahim verses 35-41 uses the irfani method (tasawuf science) and analysis approach so that it can be seen the meaning of the material and the values ​​of spiritual education contained in surah Ibrahim verses 35-41 namely the value of faith, worship, patience, sincerity, gratitude, and morals. The relevance of spiritual education in the present context of diversity in Islam is the first meaning of the rituals of prayer, fasting, zakat, and pilgrimage. If the rapid development of technology and communication as human beings are required to commemorate each other, advise that they always do the right thing and stay away from the sin. So, current technological developments by looking at spiritual education in the face of social media which are viral can we avoid but must be multi-channel in overcoming the challenges of globalization.